Do sistema de signos a teoria do ritmo: Um olhar sobre os estudos da linguagem (From the system of signs to the theory of rhythm: A look at language studies) - Neumann, Daiane (Estudos da Língua(gem), 2013)
O presente artigo objetiva discutir acerca das reflexões e contribuições trazidas por Ferdinand de Saussure e Émile Benveniste na obra de Henri Meschonnic. Essa discussão além de nos possibilitar situá-la em um quadro epistemológico, bem como compreender sua constituição, apresenta-se como um debate profícuo na medida em que nos possibilita vislumbrar as particularidades da leitura feita por Henri Meschonnic das obras desses dois grandes mestres. Tal leitura aponta para ideias e discussões que se encontram de forma embrionária na obra destes, o que nos conduz a relê-las, observando sua riqueza e complexidade. PALAVRAS-CHAVE: Émile Benveniste. Ferdinand de Saussure. Henri Meschonnic. Teoria da linguagem. ABSTRACT This work aims to discuss about the reflections and contributions brought by Ferdinand de Saussure and Émile Benveniste in the work of Henri Meschonnic. This discussion allows us to place this work in an epistemological frame as well as to understand its constitution. This is a fruitful debate inasmuch as it makes us to see the particularity of the reading made by Meschonnic of the work of Saussure and Benveniste. This reading shows us some ideas and discussions that are in the work of both of them but in a germinal way, which leads us to reread these works in a way that makes possible to remark their importance and complexity. KEYWORDS: Émile Benveniste. Ferdinand de Saussure. Henri Meschonnic. Theory of language.